Fabrication and characterization of thin 156, 158Gd targets for nuclear fusion reaction studies. (July 2022) - Prajapat, Rinku; Maiti, Moumita; S.R., Abhilash; Umapathy, G.R.; Kabiraj, D.; Khan, S.A.; Khandelwal, Deeksha; Dawar, Anit
Abstract: Thin isotopically enriched 156, 158 Gd target foils of thickness between ≈ 100– 150 μ g /cm 2 have been fabricated. The target foils were prepared on carbon backing to provide extra support using the physical vapor deposition (PVD) technique. The fabricated target foils have been used to study the dynamics of heavy-ion induced fusion reactions using the Heavy Ion Reaction Analyser (HIRA) facility at IUAC New-Delhi, India. Due to the high melting point, the e-gun method was adopted to deposition carbon and gadolinium. During fabrication, the challenges were (i) minimal isotopic material, (ii) selection of the parting agent, and (iii) the floating process for separating the gadolinium film from the glass slides. In view of this, the first several attempts have been made with natural gadolinium oxide material to optimize specific parameters. Finally, using only ≈ 38 mg isotopically enriched material for each isotope, eight 156 Gd and twenty 158 Gd targets were prepared successfully. The nobleness of this work is that the gadolinium material was in oxide form, which provides extra stability to the fabricated targets even in the atmospheric environment. Further, various characterization techniques such as Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDS), X-ray Diffractometry (XRD), and Rutherford Back-scattering Spectroscopy (RBS), have been explored to investigate surface morphology, elemental purity, chemical composition, and thickness of the target foils. The characterizations and analysis of experimental data manifested that no such impurities were present in the fabricated target foils. Essentially, it has been observed that the fabricated thin 156, 158 Gd target foils survived against the heavy-ion ( 28, 30 Si) irradiation throughout the online fusion experiment. Highlights: Fabrication of thin isotopically enriched 156, 158 Gd foils. 156, 158 Gd target preparation for nuclear reaction studies. Physical vapor deposition of gadolinium oxides. Characterization of fabricated 156, 158 Gd foils.